Formulation of Ascorbic Acid and Betaine-based Therapeutic Deep Eutectic System for Enhanced Transdermal Delivery of Ascorbic Acid - Ji-Eun Song; Seung-Hyun Jun; Joo-Yeon Ryoo; Nae-Gyu Kang (MDPI AG, 2024)
L-ascorbic acid (AA), a potent antioxidant, is commonly used topically in the pharmaceutical and cosmetic fields. However, the incorporation of AA into topical formulations is difficult because of its highly unstable nature and relatively poor skin permeability. In this study, we propose an alternative strategy for improving the solubility and topical delivery of AA through its conversion to a therapeutic deep eutectic system (THEDES). AA and betaine (Bet)-based THEDESs were prepared at certain molar ratios and characterized using polarized optical microscopy, Fourier transform infrared spectroscopy, and differential scanning calorimetry. Solubility tests showed that AA in the form of THEDES was readily soluble in various polyols (glycerin, 1,3-butylene glycol, dipropylene glycol, and 1,3-propanediol) at a high concentration (approximately 40%). Furthermore, compared to AA alone or the physical mixture of AA and Bet, AA-based THEDES significantly enhanced AA delivery through porcine skin. In an in vivo human study, THEDES-containing serum reduced the markers of aging and induced an even skin tone. These findings indicate the utility of AA and Bet-based THEDES as novel transdermal delivery systems for AA. Furthermore, our approach also showed good extension to developing gluconolactone, a well-known natural antioxidant, and Bet-based THEDES, showing potential application in transdermal delivery systems.